STUDY OF L/D RATIO EFFECT ON RESIDUAL HOOP STRESS EVOLUTION IN POLYETHYLENE PIPE - BOUCHAKHCHOUKHA, Soumia (Biopolymer Applications Journal, 2024)
In extrusion process of polyethylene tubes, it is known that residual stresses are the consequences of manufacturing process, which requires homogeneous geometric dimensions of diameter and thickness. These impose rapid cooling from the outer tube surface. Ring specimens’ were cut along a generatrix from a High Density Polyethylene (HDPE) tube to evaluate the residual stress evolution. Technique used in experiments as presented in a later study, involves on assessing residual deformation as function of ratio (L/D) over a period of time. Then, after determining the creep modulus, residual stress was measured for each ratio (L/D). Deformation values increase towards a plateau after 120h, showing a trend approaching a constant over time. This result is corroborated further by L/D=2, the greater is the diameter, the more this pattern is supported. We can presume that the deformations progress towards a condition of plane deformation. Strain-time curves show typical creep behavior of semi-crystalline viscoelastic materials such as HDPE. Results indicate that the calculated residual hoop stress is negative. In plastic pipe manufacturing, low quench water temperature results in high compressive residual stress at the outer pipe surface.